Carbenoxolone enhances TRAIL-induced apoptosis through the upregulation of death receptor 5 and inhibition of gap junction intercellular communication in human glioma - Yulyana, Yulyana; Endaya, Berwini B; Ng, Wai H; Guo, Chang M; Hui, Kam M; Lam, Paula Y P; Ho, Ivy A W (Stem cells and development, 2013)
Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) has been used extensively in cancer therapy. However, more than half of glioblastoma multiforme are insensitive to the apoptotic effect of TRAIL. Improvement in therapeutic modalities that enhances the efficacy of TRAIL in glioma is much sought after. In this study, we combined the tumor selectivity of TRAIL and tumor-homing properties of mesenchymal stem cells (MSC) with gap junction (GJ) inhibitory effect of carbenoxolone (CBX) to target orthotopic glioma. MSC were engineered to express TRAIL (MSC-TRAIL) by incorporating the secretable trimeric form of TRAIL into a Herpes Simplex Virus (HSV) type I amplicon vector. Our results showed that combined treatment of MSC-TRAIL and CBX enhanced glioma cell death, especially in three primary human glioma isolates, of which two of those are marginally sensitive to TRAIL. CBX enhanced TRAIL-induced apoptosis through upregulation of death receptor 5, blockade of GJ intercellular communication, and downregulation of connexin 43. Dual arm therapy using TRAIL and CBX prolonged the survival of treated mice by ~27% when compared with the controls in an intracranial glioma model. The enhanced efficacy of TRAIL in combination with CBX coupled with the minimal cytotoxic nature of CBX suggested a favorable clinical usage of this treatment regimen.